Borneo ethnomathematics: Developing a mathematics test instrument based on local culture - Andina Nurul Wahidah; Yumi Sarassanti; Putri Kusuma Wardani (State Islamic University of North Sumatra, 2026)
This study aimed to develop a culturally contextualized mathematics assessment instrument for Grade XI students by integrating Borneo ethnomathematics into mathematics assessment practices. This study employed a research and development (R&D) method using a modified model proposed by Wilson, Oriondo, and Antonio, consisting of three stages, namely test design, pilot testing, and test assembly. The study involved Grade XI students at MA Raudhah Islamiyah, Mempawah Regency, who were selected using a non-probability sampling technique. Data were collected through test administration and analyzed using SPSS and ANATES to examine item validity, reliability, difficulty index, discrimination index, and distractor effectiveness. The results indicate that the developed instrument meets the criteria for a high-quality assessment tool. Most items demonstrated high validity, with only a few requiring minor revisions. The instrument showed good discrimination (0.67) and a moderate difficulty level (0.66), indicating its effectiveness in differentiating students' mathematical abilities. In addition, 49% of the distractors functioned effectively. These findings suggest that integrating local cultural contexts into assessment design can produce valid and reliable instruments while enhancing the relevance of mathematics assessment for students. Therefore, the developed instrument can serve as an alternative assessment tool that promotes both conceptual understanding and cultural awareness in mathematics learning.